Recursos biológicos - Fabien Milanovic (Revue d'anthropologie des connaissances)
This text introduces the special issue on biological resources. The rise of molecular biology and bioinformatics, the sequencing of the genome of an ever-increasing number of organisms, as well as the evidence of the loss of biological diversity on earth, all give biological resources a leading role that it is indeed relevant to question. One of the objectives of this special issue is to document the increase of (human) power over life, the "bio-power" that Foucault referred to. To account for this, this introductory text adopts a transversal point of view by exploring the issues that concern various forms of life (plant, animal and human). Three transversal stakes of knowledge related to biological resources are explained: the insertion of these resources into metrological chains that contribute to the composition of social and environmental links; the targets that they are with regard to practices intended to regulate the uses, circulation and appropriation of living organisms; and the modifications that they generate in the activities that mobilize them. Biological resources thus authorize a reflection that opens up a series of fundamental issues, relating to the environment, health, science and agro-industry. However, what about the concrete practices in which they are involved, both on a planetary scale in their relationship with biodiversity, and on human (in their relationship with health) and animal (through the place of genomics in the management of domestic species) scales? The articles in this issue address these aspects from the perspective of one of this scale.